Review of acoustic comfort evaluation in dwellings: part II—impact sound data associated with subjective responses in laboratory tests. Issue 2 (June 2018) - Vardaxis, Nikolaos-Georgios; Bard, Delphine
The concept of acoustic comfort is hardly defined and used to refer to conditions of low noise levels or annoyance based on standardized descriptors. Airborne and impact sound measurements are used to rate acoustic comfort in dwellings, but they often do not express human perception of noise or comfort. If the descriptors are statistically associated with self-reported responses, they can be used as prediction models and considered sufficient for acoustic comfort assessment. This review article presents studies that approach acoustic comfort in dwellings via the association of acoustic data and subjective responses in laboratory tests. Specifically, we investigate the cases of impact sound, since it is usually reported as the most disturbing noise source in dwellings. We also evaluated the reviewed studies with the Bradford Hill's criteria. The reviewed studies indicate that self-reported annoyance to impact sound is an important issue and it can be predicted well in overall. Various standardized descriptors are studied and associate sufficiently with subjective responses. Inclusion of low frequencies down to 50 Hz in measurements improves the association of impact sound descriptors to subjective responses. Some impact noise stimuli associate only with some descriptors but not all. From the standardized impact sources, the tapping machine is the most efficient to predict overall annoyance and the impact ball for human walking or typical impact sounds in dwellings.